Evaluation of Recombinase Polymerase Amplification assay for monitoring parasite load in patients with kala-azar and post kala-azar dermal leishmaniasis - Madhurima Roy; Arianna Ceruti; Rea Maja Kobialka; Sutopa Roy; Deblina Sarkar; Ahmed Abd El Wahed; Mitali Chatterjee (Public Library of Science (PLoS), 2023)
Background The potential reservoirs of visceral leishmaniasis (VL) in South Asia include asymptomatic and relapsed cases of VL, along with patients with post kala-azar dermal leishmaniasis (PKDL). Accordingly, accurate estimation of their parasite load is pivotal for ensuring disease elimination, presently targeted for 2023. Serological tests cannot accurately detect relapses and/or monitor treatment effectiveness, and therefore, parasite antigen/nucleic acid based detection assays remain the only viable option. An excellent option is the quantitative polymerase chain reaction (qPCR) but the high cost, technical expertise and time involved precludes its wider acceptability. Accordingly, the recombinase polymerase amplification (RPA) assay operated in a mobile suitcase laboratory has emerged not simply as a diagnostic tool for leishmaniasis but also to monitor the disease burden. Methodology/Principal findings Using total genomic DNA isolated from peripheral blood of confirmed VL cases (n = 40) and lesional biopsies of PKDL cases (n = 64), the kinetoplast-DNA based qPCR and RPA assay was performed and parasite load expressed as Cycle threshold (Ct) and Time threshold (Tt) respectively. Using qPCR as the gold standard, the diagnostic specificity and sensitivity of RPA in naïve cases of VL and PKDL was reiterated. To assess the prognostic potential of the RPA, samples were analyzed immediately at the end of treatment or ≥6 months following completion of treatment. In cases of VL, the RPA assay in terms of cure and detection of a relapse case showed 100% concordance with qPCR. In PKDL following completion of treatment, the overall detection concordance between RPA and qPCR was 92.7% (38/41). At the end of treatment for PKDL, 7 cases remained qPCR positive, whereas RPA was positive in only 4/7 cases, perhaps attributable to their low parasite load. Conclusions/Significance This study endorsed the potential of RPA to evolve as a field applicable, molecular tool for monitoring parasite load, possibly at a point of care level and is worthy of consideration in resource limited settings. Author summary Visceral leishmaniasis (VL) or kala-azar caused by the digenetic parasite Leishmania donovani is a fatal form of leishmaniasis, unless treated. In South Asia, approximately 10-20% of apparently cured cases of VL develop a dermal sequela termed post kala-azar dermal leishmaniasis (PKDL). It presents with macular or papulonodular lesions that harbour Leishmania parasites. Importantly, these cases of PKDL in addition to asymptomatic and relapsed VL cases serve as mobile disease reservoirs and sustain disease transmission. In macular PKDL, that presently comprise over 50% of cases, the diagnosis is particularly challenging as parasites are often not detectable by microscopy. Accordingly, development of strategies for molecular diagnosis is one of the major foci of the ongoing leishmaniasis elimination programme targeted for 2023, that aims to decrease the burden to <1/10,000 cases of VL at the block/zilla level. Serological tests have limited applicability when it is necessary to distinguish present from past infection of VL, and in cases of PKDL when the positivity maybe due to a past history of VL. An excellent option is the quantitative polymerase chain reaction (qPCR) but limitations for its wider field applicability include the high cost, technical expertise and time factor. Accordingly, an urgent need exists for availability of field applicable molecular tests. The RPA tested in this study could well be the desired game-changer as it provided accurate diagnosis of VL and PKDL, can be performed in a primary health centre, and demonstrated the potential to be a monitoring tool for parasite load after treatment, that eventually can accelerate achieving the end-goal of elimination of leishmaniasis.